Heartmind Literacy: Compassionate Imagining & The Four Brahmavihāras - Eppert, Claudia (Paideusis, 2010)
This paper addresses the primacy of reason over emotion in much of Western philosophy and education. It brings Theravadan Buddhist wisdom to bear upon Western philosophical and educational conceptions of emotion, empathy, and compassion. More specifically, it discusses the four Brahmavihāras, or Divine Abodes. These abodes are considered boundless states of heartmind awareness that dismantle the bifurcation of mind/emotion and embody ideals of social engagement and peace. If cultivated, or dwelled in, they can overturn negative and destructive impulses, freeing the mind from greed, hatred, and delusion. They include Mettā, or loving-kindness, Karunā, or compassion, Muditā or sympathetic joy, and Uppekā or equanimity. In some respects, these abodes reflect aspects of contemporary Western understandings of empathy and compassion. However, they also elaborate upon and differ significantly from these understandings. North American learning outcomes, particularly in such areas as English language arts and peace education, seek to support the cultivation of emotional literacy in students with the hopes that such cultivation will initiate and enhance responsive and responsible relations with self, other, and environment. Insight into these abodes can consequently shed light on possibilities for deepening ethical, emotional, and educational engagement in North America.